PENGARUH MODEL PEMBELAJARAN INQUIRY TRAINING TERHADAP KETERAMPILAN PROSES SAINS PADA PEMBELAJARAN FISIKA - Sitepu, Dewi Ratna Pertiwi; Ginting, Eva Marlina (Universitas Negeri Medan, 2017)
This study aimed to know the effect of science process skills of students among the Inquiry Training (IT). This research is quasi- experimental study using pre-test and pos-test design. The population study of class X SMA Negeri 7 Tanjungbalai. Techniques that used to gain a simple is cluster random sampling, with a sample of two classes, class X-l as an experimental class and class X-4 as an convensional class. The instruments of this study were the science process skills test in the form of an essay test as many as six items, the affective, and psikomotoric was used observasion sheet. The analysis results showed that physics science process skills use Inquiry Training (IT)is different and showed better result compared with conventional learning model.